A study on the effective substance of the Wu-tou formula based on the metabonomic method using UPLC-Q-TOF-HDMS. Issue 11 (13th November 2015) - Xu, Tengfei; Liu, Shu; Zhao, Jiadi; Feng, Guifang; Pi, Zifeng; Song, Fengrui; Liu, Zhiqiang
<x xml:space="preserve">Abstract</x> To elucidate the mechanisms of five single herbs in the Wu-tou Formula, the treatment effects were evaluated on AIA rats based on the pathological variation, serum biochemical parameters and using a metabonomic method.